Konsumsi Bahan Makanan Sumber Karbohidrat dan Buah Indeks Glikemik Tinggi dengan Kejadian DM - Kasmiyetti Kasmiyetti; Dian Febry Yomi (Jurnal Sehat Mandiri, 2018)
Diabetes Mellitus occupy as the fourth largest cause of death in Padang. Based on data from Puskemas Nanggalo Padang in 2013, there were 1.012 people (2.7%) who suffered from diabetes mellitus. The glycemix index is defined as the level of food according to their effect on blood sugar levels. The aim of this research was to determine the relationship of consumption food sources of carbohydrates and fruit high glycemic index of diabetes mellitus tipe II outpatients in Puskesmas Nanggalo Padang in 2016. Using cross sectional design, the participants of this research were taken with accidental sampling method, as may as 50 peoples. Data of patients were collected through interviews, while the consumption patterns measure by using the Form Food Frequency (FFQ). The statistical test used is chi-square test with 95% confidence level. The results of analysis there are significant correlation between consumption food sources of high-glycemic carbohydrate with the incidence of diabetes mellitus tipe II, there are no significant correlation between consumption food sources of high-glycemic fruit with the incidence of diabetes mellitus. Based on the results, the health center was suggested to provide a nutrition counseling of glycemic index and refer diabetes patients to a dietitian for get an education about dietary management to reduce the incidence of diabetes mellitus. Keywords: